1976
DOI: 10.1093/ajcn/29.12.1359
|View full text |Cite
|
Sign up to set email alerts
|

Urinary creatinine excretion and lean body mass

Abstract: In a group of 34 adult and child subjects a high correlation (r = 0.988) was found between lean body mass, as determined by potassium-40 counting, and urinary creatinine excretion. The effect of technical errors was reduced by averaging the results of two or three 40K assays on each subject, and by making consecutive 3-day collections of urine. It appears that one can make a reasonable estimate of lean body mass from urinary creatinine excretion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
181
0
8

Year Published

1985
1985
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 449 publications
(193 citation statements)
references
References 29 publications
4
181
0
8
Order By: Relevance
“…This method generates juvenile growth trajectories that closely approximate those produced using conventional body weights (43,49). Creatinine production is specifically diagnostic of muscle mass (44,46,47,(74)(75)(76)(77), one dimension of overall body size. It is possible that there is important variance in fat mass or long bone growth not accounted for in this study.…”
Section: Discussionmentioning
confidence: 99%
“…This method generates juvenile growth trajectories that closely approximate those produced using conventional body weights (43,49). Creatinine production is specifically diagnostic of muscle mass (44,46,47,(74)(75)(76)(77), one dimension of overall body size. It is possible that there is important variance in fat mass or long bone growth not accounted for in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in lean body mass may also be estimated from changes in urinary creatinine excretion. From the equation of Forbes and Bruining, 38 the mean increase in urinary creatinine excretion of 0.71 mmol/day would correspond to an increase in lean body mass of 2.3 kg/day. The absence of clinical signs of edema supported that the increase in lean body mass, measured by dual-energy x-ray absorptiometry, actually reflected an increase in muscle mass.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-four hour urinary creatinine excretion is strongly correlated with lean body mass (LBM). In one study, where LBM was calculated by estimating total body potassium, a correlation coefficient of 0.988 was found between LBM (measured in either sex) and urinary creatinine excretion (Forbes & Bruining, 1976). Other studies cited by Forbes and Bruining (1976) reported correlation coefficients of between 0.72 and 0.99 for LBM, but weight appears to be less well correlated.…”
Section: Measures Of Completeness Of 24-hour Urine Collectionsmentioning
confidence: 99%
“…In one study, where LBM was calculated by estimating total body potassium, a correlation coefficient of 0.988 was found between LBM (measured in either sex) and urinary creatinine excretion (Forbes & Bruining, 1976). Other studies cited by Forbes and Bruining (1976) reported correlation coefficients of between 0.72 and 0.99 for LBM, but weight appears to be less well correlated. Bleiler and Schedl (1962) reported a correlation coefficient of 0.5 between estimates of metabolically-effective tissue derived from functions of body weight, and creatinine excretion.…”
Section: Measures Of Completeness Of 24-hour Urine Collectionsmentioning
confidence: 99%